Cost Benefit Analysis of petrol grade bioethanol production in South Africa - Moodaly, Asogan (My University, 2014)
South Africa has one of the highest unemployment rates in the world, and it is in this context that the Accelerated and Shared Growth Initiative of South Africa (“ASGISA”) promoted biofuels as a job creation initiative. However, a socioeconomic Cost Benefit Analysis (“CBA”) needs to be carried out to determine if an industry needs fiscal support; and whether said industry generates a net benefit to the economy and society when externalities are taken into consideration. The CBA focussed on bioethanol production from grain sorghum. Secondary data in terms of historic fuel pricing from the Department of Energy, capital costs and input costs from the Department of Energy, grain pricing from SAGIS, inflation rates from StatsSA and externality estimates from the literature were used to populate five Excel models. The five models comprised two financial models (with and without incentives) for two individual bioethanol plants, as well as a consolidated industry socio-economic model. The results of the modelling confirmed that the industry does require incentives in order to be viable from a private investor perspective; and that the currently proposed 15% ROA incentive model generates acceptable returns for investors with a real hurdle rate of 6%. The socio-economic model confirmed that there is an 86.644% probability of the industry creating a net socio-economic benefit to South Africa if energy security, greenhouse gas impacts, tailpipe emission impacts and emission impacts of feedstock production and bioethanol production are taken into account. The benefit was calculated against a real social discount rate of 8%. The macro-economic benefits such as job creation and improvements to balance of payments are yet to be quantified and are recommended for further research. The bioethanol production industry is worthy of Government support due to the net socio-economic benefit to South Africa.
MBA thesis
Keywords: Bioethanol; Cost-benefit analysis